POTENTIAL FOR USE OF COW URINE LIQUID ORGANIC FERTILIZER AS PLANT NUTRITION IN DRIP HYDROPONIC SYSTEMS - Damayanti, Elsa; Syamsia, Syamsia; Rosanna, Rosanna; Hakim, Irma; Mado, Irwan (Fakultas Pertanian, Universitas Janabadra, 2024)
AB mix is an nutrient that is commonly used for hydroponic system, but the price is expensive so it requires an alternatve to using liquid organic fertilizer. Thies research aims to determine the potential of organic fertilizer as a nutrient for the growth of kale, pakchoy and lecttuce in a wick hydroponic system. Thies research was prepared using aspilt plot design (SPD) with the main plot consisting of AB Mix 5 ml/liter (N1), liquid organic fertililizer cow urine 40 ml/liter (N2), liquid organic fertililizer cow urine 80 ml/liter (N3). The subplots consist of kale (T1), pakchoy (T2), and lettuce (T3). The parameters observed were plant height, number of leaves, root length, plant fresh weight. The results of this research show that the nutrients from liquid organic fertilizer from cow unire and AB mix have no significant effect on the growth of kale, pakchoy and lettuce in the drip hydroponic system. A dose of liquid organic fertilizer from cow urine of 80 ml/liter gave the best average results on plant height, number of leaves and fresh wight of kale, pakchoy and lettuce, but the results obtained were lower when compared with the application of AB mix. The dosage of cow urine liquid organic fertilizwer still needs to be increased to produce the best plant growth and production in the drip hydroponic system